Astroblastoma: a distinct tumor entity characterized by alterations of the X chromosome and MN1 rearrangement. (9th November 2017) - Hirose, Takanori; Nobusawa, Sumihito; Sugiyama, Kazuhiko; Amatya, Vishwa J.; Fujimoto, Naomi; Sasaki, Atsushi; Mikami, Yoshiki; Kakita, Akiyoshi; Tanaka, Shinya; Yokoo, Hideaki
Abstract: Astroblastoma is a rare, enigmatic tumor of the central nervous system (CNS) which shares some clinicopathologic aspects with other CNS tumors, especially ependymoma. To further clarify the nature of astroblastoma, we performed clinicopathologic and molecular genetic studies on eight cases of astroblastoma. The median age of the patients was 14.5 years, ranging from 5 to 60 years, and seven of the patients were female. All tumors arose in the cerebral hemisphere and radiologically appeared to be well‐bordered, nodular tumors often associated with cystic areas and contrast‐enhancement. Six of the seven patients with prognosis data survived without recurrences during the follow‐up periods ranging from six to 76 months. One patient had multiple recurrences and died six years later. All tumors exhibited salient microscopic features, such as being well demarcated from the surrounding brain tissue, perivascular arrangement of epithelioid tumor cells (represented by "astroblastic" pseudorosettes, trabecular alignment, and pseudopapillary patterns), and hyalinized blood vessels. Immunoreactivity for GFAP, S‐100 protein, Olig2, and EMA was variably demonstrated in all tumors, and IDH1 R132H and L1CAM were negative. Array comparative genomic hybridization revealed numerous heterozygous deletions on chromosome X in the four tumors studied, and break‐apart fluorescence in situ hybridization demonstrated rearrangement of MN1 in five tumors with successful testing. The characteristic clinicopathologic and genetic findings support the idea that astroblastoma is distinct from other CNS tumors, in particular, ependymoma. In addition, MN1 rearrangement and aberrations of chromosome X may partly be involved in the pathogenesis of astroblastoma.